2020
DOI: 10.1002/ajpa.24153
|View full text |Cite
|
Sign up to set email alerts
|

Intraspecific variability in human maxillary bone modeling patterns during ontogeny

Abstract: Objectives: This study compares the ontogenetic bone modeling patterns of the maxilla to the related morphological changes in three human populations to better understand how morphological variability within a species is established during ontogeny at both micro-and macroscopic levels. Materials and methods: The maxillary bones of an ontogenetic sample of 145 subadult and adult individuals from Greenland (Inuit), Western Europe (France, Germany, and Portugal), and South Africa (Khoekhoe and San) were analyzed.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
10
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(14 citation statements)
references
References 89 publications
0
10
1
Order By: Relevance
“…The bone remodeling maps correspond to the extreme individuals along the first PLS axis et al, 1980). In general, the anterior maxilla has a prevalence of resorption at early ages with an increase in deposition among adults (Brachetta-Aporta et al, 2019a, 2019bEnlow & Bang, 1965;Kurihara et al, 1980;Martinez-Maza et al, 2013;Schuh et al, 2020). We found that in the Chubut sample, the extension of resorption across the alveolar process persists into adulthood, which could be related to the high load demands among hunter-gatherers (Brachetta-Aporta et al, 2019a).…”
Section: Discussionmentioning
confidence: 57%
See 4 more Smart Citations
“…The bone remodeling maps correspond to the extreme individuals along the first PLS axis et al, 1980). In general, the anterior maxilla has a prevalence of resorption at early ages with an increase in deposition among adults (Brachetta-Aporta et al, 2019a, 2019bEnlow & Bang, 1965;Kurihara et al, 1980;Martinez-Maza et al, 2013;Schuh et al, 2020). We found that in the Chubut sample, the extension of resorption across the alveolar process persists into adulthood, which could be related to the high load demands among hunter-gatherers (Brachetta-Aporta et al, 2019a).…”
Section: Discussionmentioning
confidence: 57%
“…The gray lines represent the consensus and the black lines represent the shapes at the extremes of the first PLS axis. The bone remodeling maps correspond to the extreme individuals along the first PLS axis origin, suggesting that there is a common sequence of bone remodeling changes associated with facial growth in human populations (Enlow & Bang, 1965;McCollum, 2008;Schuh et al, 2020).…”
Section: Discussionmentioning
confidence: 92%
See 3 more Smart Citations